GAN: a platform of genomics and genetics analysis and application in Nicotiana. (21st February 2018) - Yang, Shuai; Zhang, Xingwei; Li, Huayang; Chen, Yudong; Yang, Long
Abstract: Nicotiana is an important Solanaceae genus, and plays a significant role in modern biological research. Massive Nicotiana biological data have emerged from in-depth genomics and genetics studies. From big data to big discovery, large-scale analysis and application with new platforms is critical. Based on data accumulation, a comprehensive platform of Genomics and Genetics Analysis and Application in Nicotiana (GAN) has been developed, and is publicly available at http://biodb.sdau.edu.cn/gan/ . GAN consists of four main sections: (i) Sources, a total of 5267 germplasm lines, along with detailed descriptions of associated characteristics, are all available on the Germplasm page, which can be queried using eight different inquiry modes. Seven fully sequenced species with accompanying sequences and detailed genomic annotation are available on the Genomics page. (ii) Genetics, detailed descriptions of 10 genetic linkage maps, constructed by different parents, 2239 KEGG metabolic pathway maps and 209 945 gene families across all catalogued genes, along with two co-linearity maps combining N. tabacum with available tomato and potato linkage maps are available here. Furthermore, 3 963 119 genome-SSRs, 10 621 016 SNPs, 12 388 PIPs and 102 895 reverse transcription-polymerase chain reaction primers, are all available to be used and searched on the Markers page. (iii) Tools, the genome browser JBrowse and five useful online bioinformatics softwares, Blast, Primer3, SSR-detect, Nucl-Protein and E-PCR, are provided on the JBrowse and Tools pages. (iv) Auxiliary, all the datasets are shown on a Statistics page, and are available for download on a Download page. In addition, the user's manual is provided on a Manual page in English and Chinese languages. GAN provides a user-friendly Web interface for searching, browsing and downloading the genomics and genetics datasets in Nicotiana . As far as we can ascertain, GAN is the most comprehensive source of bio-data available, and the most applicable resource for breeding, gene mapping, gene cloning, the study of the origin and evolution of polyploidy, and related studies in Nicotiana . Database URL : http://biodb.sdau.edu.cn/gan/